YIELD STABILITY ANALYSIS OF BREAD WHEAT GENOTYPES IN KAZAKHSTAN (Experimental biology, 2024)
Bread wheat (Triticum aestivum L.) is a significant crop for human nutrition and global food security. Ensuring stable wheat yields is crucial, as fluctuations in production can have major effects on food availability and prices globally. We evaluated 82 bread wheat genotypes in two growing seasons using multi-environment trial analysis in Kazakhstan to identify superior genotypes using AMMI-based stability statistics. The analysis of variances (ANOVA) of AMMI showed that environmental effects largely explained yield variability (87.6 %), whereas the contribution of genotype (2.79 %) and genotype-environment interaction (8.19 %) had minimal influence. An estimated set of stability parameters showed positive correlations between each other, and these measurements can be utilized to choose stable genotypes. The mean yield of bread wheat genotypes ranged from 24.5 to 17.9 centners per ha. Genotypes 342/08 (G62), Line Р-1413m (G8), Lyutescens 54 190/09 (G54), 233/10 (G58), Bajterek 15 (G25), and Lyutescens 57 4/09 (G52) were shown to be the most stable and productive based on AMMI-based stability scores for grain yield. Breeders and farmers could use these samples as stable and high-performing genotypes in a wide range of environments in Kazakhstan.
Keywords: yield, AMMI, bread wheat, productivity, stability, multi-environment trials, genotype-environment interaction, superior genotypes.